송대 선종 전적의 민간대장경 편입과 그 의의 - 李美亭; Lee Mi-jeong (중국학보, 2020)
본 논문은 불립문자를 표방한 선종이 송대에 많은 선종 전적을 생산하고 민간대장경을 통해 특정 선적을 유통시키고자 한 의도를 역사적인 시각에서 파악한 것이다. 송대 선적 출판의 활성화는 문자선의 발흥과 밀접한 관련이 있다. 문자선은 송조의 숭문정책, 선문과 사대부와의 우호 관계, 사상계에서의 삼교회통 및 선교일치 사조 제창을 그 배경으로 발흥하였으며, 여기에 송대의 인쇄술과 출판유통 환경이 가미되어 선종 저작물 양산을 재촉시켰다. 또한 선문에서는 민간대장경을 조판하고 여기에 7종의 선종 전적을 입장시켰다. 그 7종은 『경덕전 등록』·『천성광등록』·『건중정국속등록』·『대혜보각선사어록』·『종경록』·『전법정종기』·『보교편』이었다. 즉 선종의 전등 상승을 기록한 등록류와 회통적인 선풍을 강조한 한 『종경록』, 유학의 배불로부터 선종을 보호하기 위한 『보교편』, 그리고 송대 사대부 사회에 영향력이 강했던 대혜선사의 어록으로 구성되어 있다. 이 선적들이 대장경에 입장된 것은 당시 유학계의 동향이 반영된 것이었다. 인종 시기부터 유학 개변이 본격화되고 이학 창립의 서막이 열리면서 불교는 끊임없이 강도 높은 배불 공격을 감안해야 했다. 특히 진종과 인종 대를 기점으로 불교 제종파 사이에서 선종이 우위를 차지함에 따라 배불 공격의 대상은 선종으로 집중되었다. 이와 같이 격앙된 사상계의 분위기 속에서 선문의 대장경 조판과 특정 선적의 입장은 유학 일존 사회로 접어드는 시점에서 유학을 상대로 자신들의 입장을 표명해 선종을 보호함과 동시에 선적 유통을 통해 국내외로 선풍을 널리 전파하고자 한의도가 엿보인다. 그 결과 대장경을 통한 선적의 유통은 남송선의 유행을 초래함에 따라 주자학 시대로 진입한 이후에도 유학과 관계에서 생존할 수 있었으며, 또한 선종이 불교의 대표로서 그 위치를 고수할 수 있었다. This study is to understand the intention of the Chan sect, which advocated transmission outside the scripts(不立文字), to produce many Chan texts in the Song Dynasty(960~1279) and to distribute specific Chan texts through the private edition Tripitaka. The activation of the publication of the Song Dynasty’s Chan texts is closely related to the rise of Literary Chan(文字禪). There are four reasons why Literary Chan became popular in the Song Dynasty. The first is the policy of worshiping the literature of the Song Dynasty. Second, it was for friendly relations with Scholar~official(士大夫). Thirdly, the theory of harmony between the three religions became popular. Fourth, the trend of the Convergence of Chan and the Teachings(禅教一致) was asserted. Against this background, Literary Chan which became popular promoted the production of many Chan texts based on the publishing culture of the Song Dynasty. And For the first time in Chan sect, the private edition Tripitaka was typeset. This Tripitaka contains seven types of Chan texts, which were Jingde Chuandeng Lu(景德傳燈錄), Tian sheng guang deng lu(天聖廣燈錄), Jian zhong jing guo xu deng lu(建中靖國續燈錄), Dahui Pujue chanshi yulu(大慧普覺禪師語錄), Zong Jing Lu(宗鏡錄), Chuan Fa Zhengzong Ji(傳法正宗記), and Fu jiao bian(輔敎編). These Chan texts represent the characteristics of the Chan sect in the Song Dynasty and were written to emphasize the Transmission of the Lamp(傳燈) of the Chan sect and to protect Buddhism from Confucianism. Buddhism had to endure the attack of Confucianism because the innovation of Confucianism began in earnest in the world of thought from the time of Emperor Renzong. The Buddhist attacks by Confucianism were concentrated on Chan sect, as Chan sect had the highest position among the Buddhist denominations based on the times of Emperors Zhenzong and Renzong. The reason why the Chan sect typed the private edition Tripitaka in such an exasperated atmosphere and included seven types of Chan classics in the Tripitaka was to protect the Chan sect from Confucianism. As a result, even when the era of Neo-Confucianism began, Chan in the Southern Song Dynasty became popular in East Asia. This aspect enabled Chan sect to survive in the relationship between Confucianism and Buddhism and to maintain its position as a representative of Buddhism.